PERLINDUNGAN HUKUM TERHADAP KORBAN VICTIM BLAMING DALAM ALIRAN REALISME HUKUM PADA KASUS KEKERASAN SEKSUAL - Putri, Angely Lina; Kusnadi, Sekaring Ayumeida (Legal Standing : Jurnal Ilmu Hukum, 2024)
Victims of sexual violence do not receive justice and legal protection, but instead receive victim blaming behavior from society. Legal protection for victims and finding the role of legal realism in overcoming victim blaming behavior is very necessary. Therefore, this research aims to understand legal protection for victims of sexual violence by victim blaming based on realism. This research uses a normative juridical method. By using a statutory approach and a conceptual approach. Violence against women is a violation of human rights that must be condemned and acted upon. The Indonesian government has issued various laws and regulations to protect women from violence, discrimination and intimidation. The role of legal realism is to control social perceptions so as not to blame victims for the crimes they experience. This research provides an understanding of sexual violence which causes victim blaming, actions and explains legal protection rules and legal realism to provide direction to the public so that they no longer blame the victim for the crimes that happened to him.